(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2019)
Introduction. The SDR technology makes it possible to build multichannel signal receivers for replacing single-channel devices. In this the amount of real time calculations grows considerably. For these calculations it is expedient to apply parallel computations based on the multi-core central and graphic processors. The theoretical efficiency evaluation of the such receivers ignores many factors. The purpose of the article is an experimental efficiency evaluation of the SDR multichannel signal receivers’ construction. Modeling, analysis and testing. The multichannel research firmware receiver consisted of an SDR receiver, a USB controller and a computer. On a computer in a single server shell worked functionally completed software signal processingmodules.They provided reception of IQ-samples from the SDR receiver, their transfer to zero frequency, low-frequency filtration with decimation of the received samples. The experimental dependences of the maximum number of receiving channels from the decimation coefficient are obtained. At a decimation coefficient from 20 to 100 dependencies are hyperbolic, and from 100 to 10000 dependencies are directly proportional. The obtained dependences on the direct proportional section are approximated by the method of least squares. For a selected hardware platform, the proportionality coefficient is 6,1 for filters from 61 to 1001 order and 0,8 for filters from 1001 to 3901 order. Conclusions. It’s possible to increase the number of receiving channels by: increasing the decimation coefficient. The group signal and receiving channel spectrum bandwidth are the source data. Therefore, there is no possibility to increase the number of receiving channels by the decimation coefficient; decreasing filter order. The signal filtering quality depends from the filter order. Therefore, the choice of the filter order requires a compromise. The adequacy of the selected filter order to ensure a qualitative filtration with a given decimation coefficient is experimentally evaluated by the ratio of the given filtration band to the received. The obtained dependencies confirm the theoretical data: to ensure a high-quality filter with the increase of the decimation coefficient the order of the filter should be increased. With a fixed decimation coefficient, in order to achieve qualitative filtration, the order of the filter should be increased. It’s will reduce the number of receiving channels. To increase the number of receiving channels it’s necessary to reduce the order of the filter, which will lead to deterioration of the filtration quality.